NIVELES DE PRODUCCION Y VENTAS EN LA EMPRESA “MONTCLAIR” DE LA CIUDAD DE GUAYAQUIL - ALCOCER ARIAS, WILLIAN PATRICIO (2018)
Montclair "the name you saw the man" is a company that is dedicated to the preparation and development of all types of clothing such as: suits, jackets, pants, shirts, etc. This brand of clothing is well known for its quality fabric and the great finish that garments have, Montclair is located in the city of Guayaquil in the streets "Boyacá 1321 and Luque - Mall del Sol, local B94 - Luque 419 and Escobedo - Escobedo 1507 and Aguirre.